An Exploration of Within-Cultural Differences of a Culture-specific Syndrome: The Case of Brazilian jeitinho. (December 2022) - Pilati, Ronaldo; Fischer, Ronald
To what extent are cultural syndromes invariant within nations or can we identify within-cultural variability in structure and endorsement of cultural syndromes? These questions are central to a) recent discussions around the relevance of nation-states in cultural vs. geographical psychology and b) explorations of how cultural syndromes described in anthropological research are endorsed by individuals within and across regions within the country. We report data on Brazilian jeitinho, an informal problem-solving strategy that is central to Brazilian culture but may show within-cultural variability as suggested in previous anthropological and sociological research. Using a large online sample ( N = 1259) we found evidence of full score equivalence for two multi-dimensional jeitinho measures across the most populous Brazilian regions, suggesting that respondents interpret the instruments similarly. Second, we found no practically meaningful mean differences: jeitinho was endorsed equally across all regions of the country. Finally, we found some small but consistent associations with demographic variables, notably gender, age, and education differences. We need to pay greater attention to behavioral functionality at individual level—the social position of individuals within the system rather than geographical boundaries.